2021
DOI: 10.1021/jacs.1c09979
|View full text |Cite
|
Sign up to set email alerts
|

Linear Conjugated Polymers for Solar-Driven Hydrogen Peroxide Production: The Importance of Catalyst Stability

Abstract: Hydrogen peroxide (H2O2) is one of the most important industrial oxidants. In principle, photocatalytic H2O2 synthesis from oxygen and H2O using sunlight could provide a cleaner alternative route to the current anthraquinone process. Recently, conjugated organic materials have been studied as photocatalysts for solar fuels synthesis because they offer synthetic tunability over a large chemical space. Here, we used high-throughput experiments to discover a linear conjugated polymer, poly­(3-4-ethynylphenyl)­eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(136 citation statements)
references
References 38 publications
2
131
2
1
Order By: Relevance
“…High-throughput experiments have been recently conducted to rapidly screen many linear polymer photocatalysts for photocatalytic production of H 2 O 2 . 32 This approach can accelerate the discovery of organic moieties toward the molecular-level design of high-efficiency polymer photocatalysts for overall photosynthesis of H 2 O 2 . The progress can be further expedited if robotic chemists can participate in the design and synthesis of polymer photocatalysts by integrating with advanced theoretical calculations (e.g., time dependent-DFT, nonadiabatic molecular dynamics, and machine learning).…”
Section: ■ Perspective and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput experiments have been recently conducted to rapidly screen many linear polymer photocatalysts for photocatalytic production of H 2 O 2 . 32 This approach can accelerate the discovery of organic moieties toward the molecular-level design of high-efficiency polymer photocatalysts for overall photosynthesis of H 2 O 2 . The progress can be further expedited if robotic chemists can participate in the design and synthesis of polymer photocatalysts by integrating with advanced theoretical calculations (e.g., time dependent-DFT, nonadiabatic molecular dynamics, and machine learning).…”
Section: ■ Perspective and Outlookmentioning
confidence: 99%
“…In 2014, Shiraishi et al reported that the graphitic carbon nitride ( g -C 3 N 4 ), a metal-free polymer semiconductor, can produce H 2 O 2 under photoirradiation using alcohol and molecular O 2 as the proton and oxygen sources, respectively . Inspired by this seminal work, numerous organic polymer-based photocatalysts have emerged in recent years for photocatalytic production of H 2 O 2 , including g -C 3 N 4 derivatives, conjugated microporous polymers (CMPs), , covalent triazine frameworks (CTFs), , covalent organic frameworks (COFs), linear conjugated polymers (LCPs), , and resorcinol-formaldehyde (RFs) resins. Compared to their inorganic counterparts, these polymeric or “soft” materials are comprised of naturally abundant elements such as C, H, and N. Moreover, recent observation of long-lived charges in organic heterojunctions without electron/hole scavengers suggests that organic polymers are promising for driving kinetically challenging and technologically desirable redox reactions . Thus, they are up-and-coming candidates as low cost and easily processable materials for solar-driven H 2 O 2 production. …”
Section: Emergence Of Polymer Photocatalysts For Solar-driven Hydroge...mentioning
confidence: 99%
See 1 more Smart Citation
“…And a variety of organic photocatalysts have been developed, including graphitic carbon nitrides ( g ‐C 3 N 4 ), [ 10‐18 ] covalent organic frameworks (COFs), [ 19‐25 ] conjugated microporous polymers (CMPs), [ 26‐36 ] covalent triazine‐based frameworks (CTFs) [ 37‐43 ] and linear conjugated polymers (LCPs). [ 44‐52 ] Although some of them can achieve hydrogen evolution rate (HER) exceeding 10 mmol·g –1 ·h –1 , [ 22,30‐32,40,47‐49 ] the solar‐to‐hydrogen energy (STH) conversion efficiency is still very low, far from the basic requirement of 10% for their practical application. [ 2,53 ] The development of efficient photocatalysts with wide photo‐acting spectrum is still highly desirable in the field.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…With photocatalytic H 2 O 2 generation reaction proceeded, reactivity of PFBT‐PCBM binary Pdots continuously decreased together with its absorbance (Figure S13) and hydrodynamic size (Figure S14). O 2 .− [8a] and 1 O 2 [16] have been reported to degrade polymers. In our system, according to XPS data (Figure S15), the degradation of PFBT‐PCBM system is probably through the opening of thiadiazole rings in PFBT polymers caused by the photogenerated 1 O 2 as discussed in Supporting Information.…”
Section: Figurementioning
confidence: 99%